«Cultural secrets» and sports conflicts among soccer players of the Shipibo-Konibo indigenous people - Frisancho, Susana (2020)
This study explores the moral reasoning of a group of soccer players from the Shipibo-Konibo indigenous people concerning the use of various fouls and misconduct in such sport’s competitions. Through qualitative interviews, using written cards that show conflict situations in soccer games, the cultural secrets used to gain advantage over rivals are first identified. Afterwards, the beliefs and ways of moral reasoning of these players on the use of such secrets, as well as common fouls in soccer games, are examined. The results show the complex relationship that the specific cultural beliefs and worldviews have with the universal processes of moral reasoning common to people from different cultures. Authorship contribution SF: study conception and design, interviews, data interpretation, article preparation and final revision of the manuscript. ED: conception and design of the study, interpretation of the data, preparation of the article and final revision of the manuscript.